2002
DOI: 10.1097/00045391-200211000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cardiovascular Diseases

Abstract: Diabetes is a chronic illness that requires continuing medical care and patient self-management education to prevent acute complications and to reduce the risk of long-term complications. Diabetic people have cardiovascular disease (CVD) risk factors comparable to those of nondiabetics who have had a myocardial infarction or stroke. Physiologic changes in diabetic hypertensive people include endothelial dysfunction, altered platelet activity, and microalbuminuria, all of which may increase coronary heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 45 publications
0
27
0
3
Order By: Relevance
“…A profile of glucose and lipid metabolism characterized by increased plasma glucose and insulin levels (insulin resistance syndrome) increases the risk of cardiovascular disease (9). We therefore measured concentrations of glucose and insulin in plasma samples from rats fed the 2-DG and control diets under nonstress and stress conditions.…”
Section: Effects Of Dietary 2-dg Supplementation On Glucose Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A profile of glucose and lipid metabolism characterized by increased plasma glucose and insulin levels (insulin resistance syndrome) increases the risk of cardiovascular disease (9). We therefore measured concentrations of glucose and insulin in plasma samples from rats fed the 2-DG and control diets under nonstress and stress conditions.…”
Section: Effects Of Dietary 2-dg Supplementation On Glucose Regulationmentioning
confidence: 99%
“…THE RISK OF CARDIOVASCULAR disease is increased by highcalorie diets, which can lead to obesity and a metabolic syndrome characterized by insulin resistance and hypertension (9,17). Studies of mice, rats, and monkeys have shown that dietary restriction (reduced caloric intake or intermittent fasting) can increase lifespan and suppress pathogenic processes underlying the development of cancers, cardiovascular disease, and neurodegenerative disorders (1,24,33).…”
mentioning
confidence: 99%
“…Anyhow, the combination of the hypertension and diabetes results in a severe cardiac pathology than is seen with the either disease alone (Yu and Mcneill, 1991). Experimental and clinical assays have demonstrated that these patients were much more sensible to develop a generalized organ damages and stroke and such occurrence decrease the life expectance and/or compromised the life quality as well (Kaur;Regesta, 2002). The present study clearly demonstrated that streptozotocin at doses 40 or 50 mg/Kg was able to provoke a sustained hyperglycemia; however, the time course of blood glucose changes was significantly different: 28 days versus 7 days, respectively after a single injection.…”
Section: Discussionmentioning
confidence: 43%
“…This leads to cellular apoptosis and aggravated inflammation which promotes atherosclerosis through platelet aggregation, adhesion and plaque formation [10,12]. Therefore, endothelial dysfunction is a major cause of cardiovascular diseases (CVD) such as stroke, myocardial infarction (MI) and peripheral vascular disease (PVD) [13,14].…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%